Lemon Jelly : spreading lemon through the internet - Balsinha, Ana Sofia Dias Lourenço (2016)
Lemon Jelly is a fashion brand that produces and sells plastic footwear. The brand belongs to the company Procalçado, a family-owned Portuguese company that already had an experience of 40 years as a soles and footwear components producer before creating Lemon Jelly. The company is characterized by innovative production processes that allow them to produce plastic injected shoes. Lemon Jelly is mostly being sold through distributors, however it also has an online presence. The brand’s official website represents from 5 to 10% of the brand’s sales, which were up to 3 million euros in 2015. The motivation for this dissertation was to write a case study about the e-commerce strategy of Lemon Jelly. The main challenge of the brand is to understand how it can increase its online sales, being this analyzed in the Teaching Note chapter that explores some issues relevant to the main problem of the case and proposes recommendations for the future. The previous chapter, Literature Review, was designed to support the Teaching Note through theoretical concepts. It is concluded that there are several factors that can influence a brand’s online sales, therefore Lemon Jelly should select some of them according to its needs, while monitoring the results at the same time. It is also important to benchmark competitors and other players in the industry in order to keep updated through the digital evolution.